Konkursy na beneficja w Królestwie Polskim 1817-1865 : (w diecezji augustowskiej czyli sejneńskiej) - Jemielity, Witold (Prawo Kanoniczne, 1995)
The status of the church in Polish state was regulated by King Alexander I‘s edict from 6th and 8th March 1817. The edict said about a church appointment. A candidate for a perish-priest was due to take two competition examinations. The first theoretical examination included five subjects. The second one was practical, a candidate was examined about serving of the secraments and he had to write a sermon. When a candidate entered for the examination he also had to submit his life memoir and a dean’s opinion of his personal life. After the exam the examiners sent the results to a bishop who further informed the proper state commision of Religion and Public Education. If a candidate did not become a parish-priest for a period of three years he had to re-entere for the examination. When a bishop presented the name of a priest-candidate he submitted some other documents; a hand life memoir certified by the consistory, a dean’s opinion about the priest’s personal lif and his fulfilment of the church duties, a police report of a candidate’s attitude to the national uprisings, report of the results of his teaching religion at school or catechization at church, a report of the church authorities about the conditions of the presbytery he was in charge of, a report of the Court of Peace about the candidate’s registering work, a declaration that he was not a member of a secret society. Some documents concerned only the bishops who intended to charge a parish and some were valid for a definite period o f time.